Language Diversity in the Classroom and Different Subject Teachers’ Professional Competence: Some Problems and Solutions - Anspoka, Zenta (International Dialogues on Education Journal, 2016)
The relevance of research findings is connected to the problem that over the past decade Latvian schools and schools for national minorities have grown considerably with respect to their linguistic and ethnic diversity. Students who are beginning to learn the national language can be grouped into two categories, one for whom Latvian is the mother tongue and one for whom Latvian is a second or foreign language. Subject-area teachers must engage in further professional development on how to deal with the linguistic and ethnic diversity of their students; they need to help them to become familiar with the content of the different subjects. This study aims to highlight the work needed in the different subject areas and to suggest some potential realistic solutions for teachers’ professional development. Helpful in this respect are materials and methods of language theory and linguodidactics, cultural theory as well as some empirical observations of teaching in different subject areas. The professional competence of teachers with respect to linguistic and ethnic matters is connected with the necessity to recognize the individuality of students and to find out about similarities and developments in different ethnicities and cultures. It is equally important to keep in mind the balance between language and content in each subject, the organization of students’ extra-curricular time and their meaningful use of information materials and media (TV, computer, mobile phones, games with special computer programs, interactive whiteboards, etc.).